ANALISIS KINERJA DINAS KEBUDAYAAN DAN PARIWISATA PROVINSI JAWA TENGAH - Sianipar, Agahari Abadi; Lestari, Hesti; Hidayat, Zainal; Kurniawan, Landjar (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
Currently tourism become one of five sectors which giving highest contribution to Indonesia economic side. Hence, our country trying to maximize the role of tourism stakeholders. One of it is The Department of Tourism and Cultural Department Central Java. According to findings, the performance to achieve the vision is not maximum, one of the reasons are human resources factor. This study attempts to analyze the performance especially employee performance and the resistor and supporter factor. The assessment conducted with research the performance indicators that writer is use which are quality of work, quantity of work, timing, and independence of work. While the resistor factor and the supporter factor are seen from the research that writer did. This study using descriptive qualitative research methods with described the outcome of the findings and the interviews. Based on the research, the employee performance in Central Java Tourism and Cultural Department is not optimal. It is provable by the problems in all performance indicators. Then, the resistorfactor also not support the performance become optimal, so that organization should form a competitive work environment, improves the ability of employee, and coordinated with the government to solve those problems.